Perfil eletrocardiográfico e ecodopplercardiográfico de cães hígidos submetidos a tratamento com a droga antimoniato de N-metil glucamina - Bruno Abreu de Oliveira (2007)
The antimonials by parenteral injection are reported as base of treatment of many forms of leishmaniasis in human, besides being considered the first line drugs for the treatment of the visceral canine leishmaniasis in European countries. The electrocardiographic alterations in human subjected to the treatment with antimonials are already quite known, houever the incidence of these disturbances and the evolutiuon of Cardiac arrhythmias conected with use of antimonials are been reported more frequence in the last years.This study had an objective to evaluate the electrocardiographyand echoDopplercardiography profile of higid dogs with antimoniate of N-Mehil-glucamina in the dose of 50 mg/kg every 12 hours, during 30 consecutive days by subcutaneous injections. Five cross breed dogs were used, with an average estimated of 30 months. Electrocardiographyc end EchoDopplercardiographyc parameters were evaluated with an interval of 6 days and these periods were named T0,T6,T12,T18,T24 e T30. As significant results (P< 0,05) were observed in the electrocardiogram, an increase in the duration of the interval QT in T30, in consequence of a change in ventricular repolarization fase, in the echocardiogram, a reduction in the diameter of the aorta root was noticed, also in T30. Besides, the animals presented an inflamatory reaction in the region where the drug was used.